Fotograficzne wydawnictwa seryjne a ruch amatorski w XX wieku - Paśko, Jan Rajmund (Annales Universitatis Paedagogicae Cracoviensis | Studia de Cultura, 2014)
Serial publications on photography and the amateur photography in the 20th century The article discusses serial publications counted among the literature on photography, which appeared in the 20th century in Poland. Attention is paid to their suitability for amateur photographers.